Rejuvinasi Sistem Checks and Balances Dalam Sistem Ketatanegaraan di Indonesia - Indra Rahmatullah (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2013)
Rejuvenation of Check and Balance System in Statehood System in Indonesia. Instead of delegated to only a person or an Institution, State Sovereignty shall be divided into some Institutions (separation of power). The concept of Separation of power is difficult to be implemented because the each State Institution cannot share their power, therefore the concept of distribution of power has been introduced as alternative. This concept recognise Check and balances system. However, It will not guarantee harmony between State Institution. It exist the tension between State Institutions because They feel having the same authority, as seen in some cases such as between Parliament and president on Bill of head of regional election, Police Department and Commission of Eradication Corruption and the latest is the conflict between Supreme Court and Judicial Commission. DOI: 10.15408/jch.v1i2.2992